Economic advice and presidential leadership : the Council of Economic Advisers - Flash, Edward Serrill (New York : Columbia University Press, 1965)
This book is concerned with the relationship between expert knowledge and political power as revealed in the advisory function. More specifically, it discusses the relationship between the group of expert economists who compose the Council of Economic Advisers and the chief political power in the American government a represented by the President of the United States.
Includes index.
Includes bibliographical references: p. 361-372.
ne 10/07/2018
Loans
Keywords: Presidential government; United States